Early percutaneous dilational tracheostomy in COVID‐19 patients: A case report. Issue 2 (31st December 2020) - Marzban‐Rad, Saeid; Sattari, Parastesh; Heidarian Moghadam, Morteza; Azimi, Ghasem
Abstract: The need of intubation and mechanical ventilation is associated with poor prognosis in COVID‐19 patients. Herein, we present two cases of patients with COVID‐19 where intubation and mechanical ventilation failed, and therefore, percutaneous dilatational tracheotomy was performed. The usage of PDT was associated with faster and better recovery in these patients. Abstract : The need of intubation and mechanical ventilation is associated with poor prognosis in COVID‐19 patients. Herein, we present two cases of patients with COVID‐19 where intubation and mechanical ventilation failed, and therefore, percutaneous dilatational tracheotomy was performed. The usage of PDT was associated with faster and better recovery in these patients.